PENGARUH PENERAPAN SISTEM E-FILING, TINGKAT PEMAHAMAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Nurshofia, Fitri; Prasetya, Eka Rima (LPPM Universitas Bina Bangsa, 2024)
This research aims to analyze whether there is an influence between the application of the e-filing system, the level of understanding of taxation, and taxpayer awareness on taxpayer compliance at the Serpong Primary Tax Service Office. The approach used in this research is a quantitative approach. The population in this study were taxpayers registered at the Serpong Primary Tax Service Office. The data used is primary data obtained through questionnaires to respondents. The sample in this study was obtained using the convenience sampling method with the slovin formula, so that 100 samples were obtained. The data analysis method used is multiple linear regression analysis using SPSS version 20. The results of this study indicate that the application of the e-filing system affects taxpayer compliance, the level of understanding of taxation affects taxpayer compliance, and taxpayer awareness affects taxpayer compliance